FEASIBILITY OF A LONGITUDINAL AUDIOVISUAL OBSERVATION PROTOCOL TO CHARACTERIZE LUCIDITY IN ADVANCED AD/ADRD. (20th December 2022) - Gilmore-Bykovskyi, Andrea; Block, Laura; Benson, Clark; Fehland, Jess; Botsch, Meghan; Mueller, Kimberly; Coulson, Alison
Abstract: Episodes of lucidity (EL) among individuals with advanced dementia, which are predominantly reported near end of life, are clinically and potentially epidemiologically significant events. Audiovisual observation offers a valuable approach to studying EL, providing opportunities to characterize verbal/non-verbal features of EL as well as their surrounding contexts. Approaches to capturing and characterizing audiovisual data and potential verbal/non-verbal indicators of EL near end of life are lacking. We determined the acceptability and feasibility of a multi-faceted observational study protocol among people with advanced dementia near end of life incorporating longitudinal audiovisual observation, informant field interviews/logs, and case review of high likelihood EL events. Five eligible individuals were enrolled, yielding a 100% enrollment/retention rate, 54 observations/140 hours of observation across participants. Task load and usability ratings indicate study procedures with iterative refinements were feasible; surveys and qualitative appraisal from participants and staff endorse high rates of acceptability and feasibility.